Impact of Inflation and City Minimum Wages on Human Development Index in Indonesia - Herman Herman (Husnayain Business Review, 2021)
The aim of this study to knowing the impact of inflation and the city's minimum wage on the human development index in the city of Pekanbaru. The data used are Human Development Index, Inflation, and City Minimum Wages from 2010 to 2020. The data were analyzed using SPSS Version 25. The findings of this study are partially, inflation has no effect on the human development index in the city of Pekanbaru, while the city's minimum wage has a significant effect on the human development index in the city of Pekanbaru. while simultaneously that inflation and the city's minimum wage affect the human development index in the city of Pekanbaru. and the magnitude of the effect of inflation and the city's minimum wage on the human development index in Pekanbaru city of 98.8%, the remaining 1.20% by other variables not included in this study.